Physicochemical characterization of starch from various varieties of sweet potato (Ipomoea batatas) - Aina Nabilla, Bandah. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The physicochemical characteristics offive sweet potato varieties were studied and compared to potato starch. The parameters studied were starch yield, amylose content, proximate content, swelling power and solubility and yneresis. The starch content offive sweet potato varieties ranged between 23.21Yrr 29.7% The Ipomoea batatas variety 4 gave the highest yield of starch (29.7%) while Ipomoea batatas variety 3 gave the lowest yield (23.2%). The amylose contents ranged between 20. J3lYrr 25.73% Amylose content of Ipomoe~ batatas variety 5 was the highest (25.73%) while starch from Ipomoea batatas showed the lowest amylose content (20.13%). The moisture contents ranged were 8. 761Yrr9. 05% The moisture content of Ipomoea batatas variety 4 was the highest (9.05%) and the lowest was Ipomoea batatas variety 1 (8.76%). The ash content varied between 0.47IYrrO.52% Ipomoea batatas variety 3 showed the highest ash content (0.52%) and the lowest ash content was found for Ipomoea batatas variety 4 (0.47%). The lipid content varied between o. 091YrrO. 12% Ipomoea batatas variety 2 gave the highest lipid content (0.12%) while the lowest was found for Ipomoea batatas variety 3 (0.09%). The protein contents were in the range of o. 171YrrO. 19% Ipomoea batatas variety 4 gave the highest protein content (0.19%) while Ipomoea batatas variety 1 gave the lowest protein content (0.17%). The swelling power ofIpomoea batatas variety 3 starch was the highest among all samples of sweet potato starches at all the temperature ranged studied while Ipomoea batatas variety 5 showed the lowest swelling power. For solubility, it was found that Ipomoea batatas variety 5 showed the highest solubility and the lowest wasfoundfor Ipomoea batatas variety 3 at all the temperature ranged studied. Syneresis for Ipomoea batatas variety 5 starch was the highest while Ipomoea batatas had the lowest value ofsyneresis tendency among the sweet potato starches studied.